Claude’s Syndrome: A Case Report of Rare Midbrain Syndrome from Bangladesh - Huq, Muhammad Rezeul; Kabir, Humayun; Chowdhury, Md Ismail; Rumi, Md Forhad; Anwar, Mahin Binte (Journal of Armed Forces Medical College, Bangladesh, 2023)
Claude's syndrome is a rare brainstem syndrome with ipsilateral third nerve palsy and contralateral ataxia. Here we present a case of a 60-year-old male with Claude's syndrome due to cerebral infarct. The patient had left-sided pupil sparing third nerve palsy with right-sided ataxia. MRI of the brain revealed infarct in the left half of the tegmentum of the midbrain. MRA of the brain was unremarkable. The patient improved gradually and was almost asymptomatic after one month. Though the syndrome was first described a century ago, it warrants particular attention from clinicians due to its rarity and atypical features. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 72-74